THE ANALYSIS OF LAKE TOBA POTENTIAL AS MICE TOURISM DESTINATIONS FOR INCENTIVE FIELD IN NORTH SUMATERA - Asmah Kartika Dalimunthe (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This study aims to find out and analyze the potential of MICE tourism in the incentive field at Lake Toba Samosir, North Sumatra. This research uses descriptive qualitative method; it is included in survey research. The results of the discussion of the research that has been carried out are: (1) Increasing facilities and infrastructure to support tourist activities (2) There are not many tourist activities so that tourists are likely to only have 1 to 2 days so that MICE tourism in the incentive sector can increase even more. (3) The Government has carried out MICE Tourism activities by carrying out annual activities such as the 2014 Lake Toba Party that can increase tourist visits to the Toba Samosir area so that MICE Tourism can be carried out well. (4) The hotel is ready to face MICE Tourism but hotel managers still need training and socialization for MICE Tourism so that hotel managers and tourism players can promote hotels to increase occupancy rates. Recommendations for increasing MICE tourism potential are: (1) Quality improvement of facilities and supporting infrastructure (2) Tourists activities ,ust be mopre diversified so the guests do not feel bored and immediately return home or immediately continue their visit to other areas, (3) The role of the government has been very good for advancing MICE Tourism in the Toba Samosir area, it would be even better if it could create an annual activity agenda such as a Sports Tournament, motorcycle crossing, mountain bike, trekking, 10 km marathon run, music concert, Batak Opera and National Culture others from various regions, proficiency shows, entertainment programs, people's harvest parties, and others. (4) To advance MICE tourism, tour operators and hotel managers still need training and dissemination of MICE implementation